Large-eddy simulations of a turbulent jet impinging on a vibrating heated wall - Natarajan, T.; Jewkes, J.; Lucey, A.; Narayanaswamy, Ramesh; Chung, Y. (2016)
High-resolution large-eddy simulations (LES) are performed for an incompressible turbulent circular jet impinging upon a vibrating heated wall supplied with a constant heat flux. The present work serves to understand the flow dynamics and thermal characteristics of a turbulent jet under highly dynamic flow and geometric conditions. The baseline circular vibrating-wall jet impingement configuration undergoes a forced vibration in the wall-normal direction at the frequency, f = 100 Hz. The jet Reynolds number is Re=DVb/νRe=DVb/ν = 23,000 and the nozzle-exit is at y/D = 2 where the wall vibrates between 0 and 0.5D with amplitude of vibration, A = 0.25D. The configuration is assembled through validation of sub-systems, in particular the method for generating the turbulent jet inflow and the baseline circular jet impingement configuration. Both time-mean and phase-averaged results are presented. The mean radial velocity increases upon positive displacement of the wall and decreases upon negative displacement but this correlation changes with increased radial distance from the stagnation point. Vortical structures are shown to play a major role in convective heat transfer even under the vibrating conditions of the impingement wall. Periodic shifts in the secondary Nusselt number peak are observed that depend upon the travelling eddy location and strength of large-eddy structures. Enhancement in heat transfer is seen in the stagnation region but this beneficial effect of vibration on heat transfer is confined to the impingement region, r/D < 1.5.